Development of a Web-Based Interactive Learning Media to Improve Students' Conceptual Understanding of Subnetting through Flipped Classroom - Dzulfikri Najmul Falah; Enjang Ali Nurdin; Yogi Prasetyo (Universitas Trunodjoyo Madura, 2026)
Subnetting is a challenging topic for vocational students because it requires understanding both network concepts and step-by-step calculation procedures. This study developed NetLearn, a web-based interactive learning media designed to support subnetting learning through structured learning paths, micro-learning content, visual explanations, gamification, and interactive CIDR, FLSM, and VLSM simulations within a Flipped Classroom setting. The novelty of NetLearn lies in the integration of these features into a single web-based platform specifically designed for vocational subnetting instruction. The research applied the ADDIE development model and involved 32 eleventh-grade Computer and Network Engineering students at a vocational high school in Bandung. Media feasibility was examined using the Learning Object Review Instrument, while students’ conceptual understanding was measured through equivalent pretest and posttest instruments. The collected data were analyzed using the Shapiro-Wilk normality test, Paired Sample T-Test, and Normalized Gain. Expert validation produced a feasibility score of 87.06%, placing the media in the highly feasible category. The implementation results indicated a significant improvement in students’ scores after using the developed media, with an average N-Gain score of 0.31 in the moderate category. These findings suggest that combining structured learning paths, interactive subnetting simulations, and Flipped Classroom activities can support students in learning subnetting in a more visual, guided, and interactive way. However, the findings should be interpreted with caution because the study used a one-group pretest-posttest design without a control group.